Matemática no ensino médio: prescrições das propostas curriculares e concepções dos professores - Godoy, Elenilton Vieira (2002)
This research is insered in a group of studies intitled The Mathematics in curricular organization: history and actual perspectives and analyzes the historical trajectory of high school courses in Brazil detaching its finalities along the time. There is a particular focus about the perfomance of the Mathematics in the high school s curriculum. Through this bibliographic and documental research were studied proposals of diferent periods detaching the curricular proposal of São Paulo State in the decade of 1980. There is a study about the nineties with reference to Parâmetros Curriculares Nacionais para o Ensino Médio PCNEM Secretariat of High School and Tecnologic of Education Ministry and makes comparisions with documents of France, Spain and Portugal. In the sequence, the work searches to identificate the thought of the teachers that are actuating in the high school with reference to concepts of contextualization and the interaction between disciplines and the ways that the teachers consider interestings. Makes a repertory about the theoretical studies in the education area of the Mathematics that can support these proposals, starting from main conceptions that guide the PCNEM, precisely with reference to ideas of contextualization and interaction between disciplines